Competency based Performance Management – The Bharat Dynamics Ltd. (BDL) Way. Issue 2 (July 2015) - Raju, N.K.; Mishra, R.K.; Sarkar, Shulagna
Bharat Dynamics Limited (BDL) a sobriquet of 'the force behind the peace' of India is a Mini Ratna (Category I) company. BDL has been initiating various interesting HR practices since inception. 'Performance' being the ultimate goal, companies have attempted to link performance management system to competency based HR initiative and BDL is one of such success legend. An attempt has been made to discuss the competency based performance management system at BDL. The paper provides a deep insight of how BDL has established 'Competency' as one of the four pillars of the HR operation as indicated by DPE and also implemented competency based HR practices as an integral part of company operations. The paper also aims to discuss the mode of performance classification at BDL. The paper shares the unique methodology of development and assessment of the BDL competency model and provides reference to companies intending to initiate competency based HR practices.